Hierarchically Structured CeO2 Catalyst Particles From Nanocellulose/Alginate Templates for Upgrading of Fast Pyrolysis Vapors - Moyer, Kathleen; Conklin, Davis R.; Mukarakate, Calvin; Vardon, Derek R.; Nimlos, Mark R.; Ciesielski, Peter N. (Frontiers in Chemistry, 2019)
Hierarchically structured porous materials often exhibit advantageous functionality for many applications including catalysts, adsorbents, and filtration systems. In this study we report a facile approach to achieve hierarchically structured, porous cerium oxide (CeO2) catalyst particles using a templating method based on nanocellulose, a class of renewable, plant-derived nanomaterials. We demonstrate the catalyst performance benefits provided by this templating method in the context of Catalytic Fast Pyrolysis (CFP) which is a promising conversion technology to produce renewable fuel and chemical products from biomass and other types of organic waste. We show that variations in the porous structures imparted by this templating method may be achieved by modifying the content of cellulose nanofibrils, cellulose nanocrystals, and alginate in the templating suspensions. Nitrogen physisorption reveals that nearly ten-fold increases in surface area can be achieved using this method with respect to commercially available cerium oxide powder. Multiscale electron microscopy further verifies that bio-derived templating can alter the morphology of the catalyst nanostructure and tune the distribution of meso- and macro-porosity within the catalyst particles while maintaining CeO2 crystal structure. CFP experiments demonstrate that the templated catalysts display substantially higher activity on a gravimetric basis than their non-templated counterpart, and that variations in the catalyst architecture can impact the distribution of upgraded pyrolysis products. Finally, we demonstrate that the templating method described here may be extended to other materials derived from metal chlorides to achieve 3-dimensional networks of hierarchical porosity.